Eosinophilic granulomatosis with polyangiitis; a distinctive presentation with myocarditis and autoimmune haemolytic anaemia: case report - Doaa Abdulwahab Mohammed Ayish; Fatma Ayish; Asayel Khamjan; Amal. H. Mohamed; Nagla Abdalghani; Osama Albasheer (Frontiers in Cardiovascular Medicine)
BackgroundEosinophilic granulomatosis with polyangiitis (EGPA) is an extremely rare type of vasculitis characterized by inflammation within small blood vessels or tissues that may cause damage to the lungs, heart, kidneys, and other organs. Here, we present a rare case of EGPA with cardiac involvement that presented with acute heart failure.Clinical findingsA 44-year-old woman with a history of bronchial asthma and sinusitis presented with fever, shortness of breath, fatigue, unintentional weight loss, and polyarthritis. Physical examination revealed bilateral basal crepitation and mononeuritis multiplex.DiagnosisThe peripheral blood smear revealed red blood cells of different sizes and shapes (dimorphic features), more eosinophils, low hemoglobin, and higher lactate dehydrogenase (LDH) levels. Cardiac magnetic resonance imaging (CMR) revealed global hypokinesia and features suggestive of myocarditis. Echocardiography showed a low ejection fraction of 25%. Thus, the patient diagnosed with EPGA and myocarditis presented with acute heart failure.InterventionsThe patient was administered high-dose corticosteroids (intravenous bolus methylprednisolone 500 mg for three days, followed by 1 mg/kg of prednisolone) and cyclophosphamide 750 mg intravenously.OutcomeAfter one months, the patient showed a marked improvement in clinical and laboratory parameters. The ejection fraction improved to 30%–40%, the eosinophil count returned to normal, and the haemolytic anaemia resolved. The patient was sent home and shifted to mycophenolate mofetil 1 g twice a day as maintenance therapy.ConclusionPatients with EGPA have a higher morbidity and mortality rate when they have cardiac involvement. The pathophysiological mechanism of cardiac involvement in EGPA warrants consideration of immunosuppressive therapy in addition to standard heart failure treatment.